Addressing the Value Management Approach in Public Construction Works: Barriers, Critical Success Factors, and Potential Risks - Mum, Nusret; Atabay, Senay; Tekin, Hamdi; Akkaya, Durmus (MDPI, 2025)
Value management (VM) is a management approach aimed at inspiring individuals, nurturing their talents, and fostering synergy and innovation, all with the objective of enhancing an organization's overall performance. This methodology seeks to reduce costs while actively engaging a diverse array of stakeholders throughout the project lifecycle. Despite its significance in construction projects, there exists a notable gap in the literature regarding the implementation of value management in public works. This study aims to identify the barriers that hinder the effective implementation of value management, as well as the critical success factors and potential risks associated with its adoption in public projects. Additionally, it assesses Turkey's readiness for implementation within the construction sector by examining awareness levels, legislative issues, and other pertinent topics. To conduct the study, a quantitative survey was administered to 337 participants from various roles within the Turkish construction sector. The findings revealed that the inherent complexity of construction projects, time constraints, and difficulties in alternative selection are the primary barriers to implementing the value management approach in public works. Regarding the critical success factors for effective VM implementation, the involvement of end users, a collaborative workshop environment, and the multidisciplinary composition of the VM team were identified as the most significant contributors to success. Additionally, the study highlighted potential risks associated with the adoption of VM in public works, including low operating efficiency, a low participation rate in tenders, and cost overruns. The discussion also addressed legislative and process-oriented strategies for the potential adoption of value management.
Keywords: value management; construction; risk; Science & Technology - Other Topics; Environmental Sciences & Ecology